Serenas e desesperadas: representações femininas na obra poética de Cecília Meireles - Silva, Roberta Donega [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The literature produced by women is increasingly winning its space in the history of literature. The number of writers, female representations and even critics and literary historians continue to grow, ensuring women ever more a solid ground in the literary world. Among the writers who already hold a renowned place in the literary canon lies Cecília Meireles. For some writers, the poetess occupies a neutral place in her poetry regarding to gender. According to this view, Cecília would favor some issues considered universal rather than topics related to the experience of being a woman. This could be explained by the fact that the writer highlights in her poems topics such as the transcendence of being, the brevity of life and in addition to that the various aspects of death, to show some examples. However, recent studies indicate that the presence of women in her writing is more evident than previously thought. The purpose of this study is to select poems in which the female presence is significant and thus seek to understand and analyze how women’s representation happens. To accomplish that, we intend to support the feminist criticism and more specifically the methodology suggested by Elaine Showalter. In addition, we also intend to observe the women figurations as social constructions. Our final goal is to contribute to the reading possibilities enrichment of Cecília Meireles’ work, offering a more analytical perspective of her poems

A literatura produzida por mulheres ganha gradativamente mais espaço na história literária. O número de escritoras, representações femininas e até mesmo de críticas e historiadoras literárias continua crescendo, garantindo um lugar cada vez mais sólido para a mulher no meio literário. Dentre as escritoras que já ocupam um lugar consagrado no cânone literário encontra-se Cecília Meireles. Para alguns escritores, a poetisa ocupa um lugar neutro em sua poesia no que diz respeito à questão de gênero. De acordo com essa visão, Cecília privilegiaria assuntos considerados universais em detrimento da temática relacionada à experiência de ser mulher. Isso se explicaria pelo fato de a escritora colocar em evidência em seus poemas assuntos como a transcendência do ser, além de tratar em vários momentos da brevidade da vida e dos vários aspectos da morte, para citar alguns exemplos. Entretanto, estudos recentes indicam que a presença feminina na obra ceciliana é mais evidente do que se supunha. A proposta deste estudo é selecionar poemas em que a presença feminina seja significativa e buscar compreender e analisar como a representação feminina acontece. Para tal, pretendemos nos apoiar na crítica feminista e, mais especificamente, na metodologia indicada por Elaine Showalter. Além disso, pretende-se observar as figurações do feminino enquanto construções sociais. Nosso objetivo final é contribuir para o enriquecimento das possibilidades de leitura da obra de Cecília Meireles, oferecendo mais uma perspectiva analítica dos poemas cecilianos
Keywords: Meireles, Cecilia 1901-1964; Poesia brasileira; Critica feminista; Mulheres e literatura; Brazilian poetry